3D-printed flexible, Ag-coated PNN-PZT ceramic-polymer grid-composite for electromechanical energy conversion. (July 2020) - Wang, Zehuan; Yuan, Xiaoting; Yang, Jikun; Huan, Yu; Gao, Xiangyu; Li, Zhanmiao; Wang, Hong; Dong, Shuxiang
Abstract: Piezoelectric ceramic materials such as Pb(Zr, Ti)O3 (PZT) based ceramics have excellent electromechanical energy conversion ability, however, their rigid and undeformed characters are not suitable for flexible electronics application. Here, we report the design of flexible (0–3) connection ceramic-polymer composite made of polydimethylsiloxane (PDMS) elastomeric matrix doped with Ag-coated PNN-PZT (0.55Pb(Ni1/3 Nb2/3 )O3 -0.135PbZrO3 -0.315PbTiO3 ) ceramic heterojunction particles, and the 3D printing method for fabricating complex three-dimensional grid architectures. It was found that the 3D-printing, non-stereolithographic grid-composite exhibits a greater flexible character after doping ceramic particles and also excellent electromechanical coupling with a piezoelectric voltage coefficient g 33 as high as 400 × 10 −3 m V N −1, which is one order of magnitude higher than that of PZT based ceramics. Under drop hammer ( 20 N) impact, it can instantly drive over 20 commercial red-LEDs lighting directly without using a charge storage capacitor. This work shows that 3D-printed flexible ceramic-polymer composite has potential to replace brittle piezoceramics for electromechanical energy conversion and touching force sensor applications, such as soft robotics, artificial muscles and biology signal identification. Graphical abstract: Image 1 Highlights: The first 3D printing piezoelectric composites based on PDMS matrix is achieved. Printed ceramic composites shows a remarkable mechanical property. 3D printed piezoelectric composites exhibits notable sensing property after poling.